Part of Material Opression: A Study On Romanticism and Stigma of The Role of Housewives and Working Mothers - Khoniq Nur Afiah; Rofah Rofah (HUMANISMA : Journal of Gender Studies, 2021)
This study aims to determine the romanticism of the mother's role and the stigma housewives, and working mothers receive. Romance towards the role of the mother often has an unfavorable impact on the mother's condition. Besides romance, stigma is also born and accepted by housewives and working mothers. The stigma continues and impacts the condition and vulnerability of a mother. This research is descriptive qualitative research and analyzed by feminist theory about mothers. The study results stated that the romanticism of the mother's role affected the workload received. This study opens a view about the need for efforts to solve the problem of romanticism in the role of mothers. It is necessary because it is helpful to prevent the occurrence of adverse effects on the condition of the mother's vulnerability. This study also found four stigmas received by working mothers and housewive such as Bachelors who only become full-time mothers, housewives: working spends husband's money, working mothers: never have time to educate children, working mothers: children are entrusted to grandmother, be a grandma's child, housewive are clumsy. Housewive enjoy life because they relax, career women like hanging out, and working mothers have minimal knowledge of kitchen and parenting matters. The two points above are important points that became the findings in this study. housewife: work spends husband's money, working mother: never has time to educate children, working mother: grandmother leaves children, be grandma's child, housewive are clumsy. Housewive enjoy life because they relax, career women like hanging out, and working mothers have minimal knowledge of kitchen and parenting matters. The two points above are important points that became the findings of this study. Penelitian ini memiliki tujuan guna mengetahui romantisme peran ibu dan stigma yang diterima oleh ibu rumah tangga dan ibu bekerja. Romantisme terhadap peran ibu sering memberikan dampak yang kurang baik terhadap kondisi ibu. Selain romantisme, Stigma juga lahir dan diterima oleh ibu rumah tangga dan ibu yang bekerja. Stigma tersebut terus diproduksi dan memberikan dampak terhadap kondisi dan kerentanan seorang ibu. Penelitian ini adalah penelitian deskriptif kualitatif, dan dianalisis dengan teori feminis tentang ibu. Hasil penelitian menyatakan bahwa romantisme peran ibu memberikan efek terhadap beban kerja yang diterima. Penelitian ini membuka pandangan mengenai perlunya upaya-upaya yang bisa menyelesaikan persoalan mengenai romantisme terhadap peran ibu. Hal tersebut diperlukan, sebab berguna untuk menghambat terjadinya dampak buruk terhadap kondisi kerentanan ibu. Penelitian ini juga menemukan empat stigma yang diterima ibu bekerja dan ibu rumah tangga seperti:  Sarjana kok yang hanya menjadi fulltime mom, ibu rumah tangga: bekerja menghabiskan uang suami, ibu bekerja:  tidak pernah memiliki waktu untuk mendidik anak, ibu bekerja: anak dititipkan nenek, jadilah anak nenek, ibu rumah tangga itu kucel. Ibu rumah tangga enak hidupnya karena hanya santai-santai, wanita karir emang hobinya nongkrong, dan ibu bekerja memiliki pengetahuan yang minim terhadap urusan dapur dan pengasuhan. Dua poin diatas menjadi poin penting yang menjadi temuan dalam penelitian ini.